LEGAL POLICIES REGARDING RELIGIOUS DELICT IN THE INDONESIAN CRIMINAL CODE - Sirait, Trinita Yulinda; Soponyono, Eko (Tadulako University, 2020)
The Indonesian nation consists of ethnic groups consisting of many tribes, races, classes, religions, and cultures that demand Indonesian people. The reality that occurred in the community was found about the contradictions between religious communities who demanded that Indonesia overcome it with formulation policies or which were part of the action through criminal law policies (criminal policy. This research aims to describe the formulation policy regarding religious offenses in Indonesia. normative that puts forward secondary data in the process of finding conclusions Article 156 and Article 156A of the Criminal Code is a state policy to assist with religious fish interest policies that have succeeded in solving the Indonesian nation, protecting the integrity and national defense of the Indonesian nation.